Young frigatebirds learn how to compensate for wind drift. Issue 1937 (28th October 2020) - Wynn, Joe; Collet, Julien; Prudor, Aurélien; Corbeau, Alexandre; Padget, Oliver; Guilford, Tim; Weimerskirch, Henri
Abstract : Compensating for wind drift can improve goalward flight efficiency in animal taxa, especially among those that rely on thermal soaring to travel large distances. Little is known, however, about how animals acquire this ability. The great frigatebird ( Fregata minor ) exemplifies the challenges of wind drift compensation because it lives a highly pelagic lifestyle, travelling very long distances over the open ocean but without the ability to land on water. Using GPS tracks from fledgling frigatebirds, we followed young frigatebirds from the moment of fledging to investigate whether wind drift compensation was learnt and, if so, what sensory inputs underpinned it. We found that the effect of wind drift reduced significantly with both experience and access to visual landmark cues. Further, we found that the effect of experience on wind drift compensation was more pronounced when birds were out of sight of land. Our results suggest that improvement in wind drift compensation is not solely the product of either physical maturation or general improvements in flight control. Instead, we believe it is likely that they reflect how frigatebirds learn to process sensory information so as to reduce wind drift and maintain a constant course during goalward movement.